SUSTAINABLE DEVELOPMENT DITINJAU DARI MATERIAL FLOW COST ACCOUNTING DAN GREEN INTELLECTUAL CAPITAL - Suhadi Hadi; An Nisa Rahmawati; Cihwanul Kirom (Universitas Wahid Hasyim, 2026)
The research aims to examine the effect of material flow cost accounting and green intellectual capital on sustainable development (a study of energy sector companies registeredwith ISSI in 2014-2023. This type of research uses a quantitative method. The sampling using a purposive sampling technique. The sample is 70 obatianed 7 companies through a 10-year observation periode. The type of data used is secondary data obatined fom annual report. Data processing uses SPSS version 25. The result of this research indicate that MFCA has a calculated value of 4,234, which is greater then the t table (4234>1,66792). The MFCA variable has a significance level of 0,000 which is smaller than the established significance (0,000<0,05). The GIC variable has a calculated value of 1,751, which is smaller than the t table (1,751<1,66792. The GIC vaiable has a significance leel of 0,084 which is greater than the established significance. The result of the F show a significance of 0,000 which is smalller than the f table which is 3,13. Keywords: Material Flow Cost Accounting; Green Intellectual Capital; Sustainable Development.